Chapter 9: The artifacts of entrepreneurial practice - Berglund, Henrik (Edward Elgar Publishing, 2022)
In this chapter we set out to complement the entrepreneurship as practice perspective by proposing a conceptualization of its central artifacts, such as business models, pitches, and prototypes. Having defined as entrepreneurial those artifacts that serve to instantiate an abstract opportunity in a way that supports its further development, we discuss entrepreneurial artifacts in terms of three broad categories: abstract, material, and narrative. Thereafter we point to some themes for further development before concluding with implications for the practice (and practice theory) of entrepreneurship.